Dylematy metodyczne badań zachowań podmiotów rynkowych w warunkach globalizacji - Kucharska, Barbara; Malinowska, Mirosława (Methodological Dilemmas of Market Entities Research Behaviour in the Conditions of Globalization, 2006)
Globalization process is a current phenomenon which becomes more and more intense. Complexity of globalization creates many methodological obstacles in research of this area. There are a lot of publications on globalization, but in a few of them relations between globalization and market entities' behaviour are presented. These relations are able to be recognised by researching the influence of particular factors related to globalization on market entities behaviour. It is not an easy task because of multidimensional and long-time character of globalization. In the article methodological problems related to research of market entities' behaviour under globalization are presented. The authors present some doubts and reflections, which emerged during the performing of the project financed by The State Committee of Research ''Market entities' behaviour in Poland under globalization conditions".
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 79-86